2004
DOI: 10.1111/j.0303-6987.2004.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenoma papilliferum with mixed histopathologic features of syringocystadenoma papilliferum and anogenital mammary‐like glands

Abstract: A case of hidradenoma papilliferum with mixed features of syringocystadenoma papilliferum (SCAP) and anogenital mammary-like glands is reported. A single, fresh red-colored nodule developed in the sulcus between the labia majora and minora of a 49-year-old Japanese woman. Histopathologically, the tumor showed epithelial lining with apocrine secretion and slight connective tissues characteristics. Our case was unique because, like SCAP, the tumor was connected to the epidermis and cystic invaginations extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
4
20
0
2
Order By: Relevance
“…4 In addition, many of those variants occur in typical MLG adenomas. 4 The only previously published case of HP with SCAP and anogenital MLGs was by Nishie et al 5 In that case, it was suggested that the neoplasm originated from anogenital MLGs and might serve as a documented example of van der Putte theory. 5 We believe that the findings they presented closely resemble those in our case, which we present as further documentation of the association between anogenital MLG and HP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In addition, many of those variants occur in typical MLG adenomas. 4 The only previously published case of HP with SCAP and anogenital MLGs was by Nishie et al 5 In that case, it was suggested that the neoplasm originated from anogenital MLGs and might serve as a documented example of van der Putte theory. 5 We believe that the findings they presented closely resemble those in our case, which we present as further documentation of the association between anogenital MLG and HP.…”
Section: Discussionmentioning
confidence: 99%
“…48 The reported case, similar to ours, presented with mixed histology of SCAP and MLGs. 5 There are also reported cases of pseudoangiomatous stromal hyperplasia in lesions of anogenital MLGs, all with complex histology. 39,45 Although the reports of simple and complex adenomas were well described in the literature, there are other reports describing breast-like glandular proliferations arising from anogenital MLGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epithelium lining the papillae is composed by a basal layer of cuboidal cells and a luminal layer of larger columnar cells showing decapitation secretion [7]. Sometimes the tumor may show a histopathology similar to syringocystadenoma papilliferum since both are closely related tumors originating from apocrine glands [8]. The differential diagnosis also includes tubular apocrine adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…sclerosing adenosis [7], hidradenoma papilliferum [8], adenomas [9,10] with one reported adenoma-carcinoma sequence [11], and carcinomas in which pagetoid growth may occur [5,12]. The carcinomas were suggested to constitute a separate entity of skin cancer, even though their variable expression of apocrine, eccrine, and mammary gland features made their classification controversial [2,6].…”
Section: Introductionmentioning
confidence: 99%